Tuberculous like lesions in lymph nodes of pigs in Pernambuco, Brazil - Langenegger, Charlotte Hubinger; Langenegger, Jerome (Pesquisa Agropecuaria Brasileira, 2014)
Tuberculous like lesions were found in the mandibular lymph nodes of 122 (15.2%) from 800 slaughtered pigs, raised in the wet costal region (Zona da Mata) and in the semiarid region (Agreste) of the State Pernambuco. The bacteriological examination allowed the isolation of 45 mycobacteria. The identification of these strains by cultural and biochemical behavior and pathogenicity tests in chicken revealed that 9 were Mycobacterium tuberculosis, 7 M. bovis, 14 M. intracellulare, 6 M. scrofulaceum, 3 M. terrae and one strain of M. gordonae, M. triviale and M. fortuitum. M. avium was not detected. Beside the mycobacteria, Corynebacterium equi was isolated from 64 (52.4%) of the 122 affected lymph nodes. In 17 cases C. equi was found associated with mycobacteria in the same lesion.